Pengaruh Kepemimpinan Kepala Desa terhadap Partisipasi Masyarakat dalam Pembangunan Desa Sruwi Kecamatan Winongan Kabupaten Pasuruan - Alfi Nuridina; Ratna Pudyaningsih; Eni Erwantiningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Leadership is the ability to persuade or influence others to achieve certain goals and the authority to establish responsibility. The role and community is consciously and voluntarily in the stage of decision making, implementation of activities, monitoring and evaluation, as well as the use of development results from the development process is called